Argentina : First Review Under the Extended Arrangement Under the Extended Fund Facility, Request for Modification of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Argentina. (IMF Staff Country Reports; Country Report ;, 2022)
First Review under the Extended Arrangement under the Extended Fund Facility, Request for Modification of Performance Criteria, and Financing Assurances Review.